PENGARUH KONSENTRASI MADU TERHADAP PERUBAHAN WARNA GIGI PADA PROSES PEMUTIHAN GIGI SECARA IN VITRO - Sigit Fitri Istanti; Endah Aryati E; Kusuma Arbianti (Odonto : Dental Journal, 2014)
Background: Needs of dental cosmetic services increased due to people's desire to get a brighter and whiter smile. Hydrogen Peroxide (H2O2) is one of bleaching substance that most commonly used. Use of H2O2 in a high concentration can cause a negative impact on the oral cavity. Honey is a natural ingredient that can whiten teeth. This study aimed to determine the effect of concentration of honey on tooth colour changes of teeth whitening process. Method: This research was an experimental in vitro study using pretest-posttest design with teeth as a research sample. 24 premolars teeth as samples were soaked in various concentration of honey (25%, 35%, 50%, 75%). The colour of teeth were measured with a spectrophotometer before and after treatment. Teeth colour were analyzed by paired samples T-test. Result: Paired T-test showed p<0.05, which means that concentration of honey affected on tooth colour changes. One way ANOVA test results showed concentrations of honey significantly affect tooth discoloration (p <0,05). Post hoc test results showed significant difference On the concentration of 25% of the concentration of honey 50%, 75%, but on a concentration of 25% honey and 35% there is no significant difference. Conclusion: From these results, it can be concluded that the concentration of honey affected on tooth colour changes in an in vitro tooth whitening process.